2018
DOI: 10.1088/2057-1976/aabab2
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitisation enhancement effect of BrUdR and Ta 2 O 5 NSPs in combination with 5-Fluorouracil antimetabolite in kilovoltage and megavoltage radiation

Abstract: This article demonstrates in vitro a synergistic effect on 9L gliosarcoma cells when exposed to bromodeoxyuridine (BrUdR) and a low concentration (100 times lower than the IC50) of 5-Fluorouracil (5-FU), in combination with x-ray irradiation. The synergy is brought about by several important factors including the x-ray beam energy, atomic number of the BrUdR (Z=35), effectiveness of 5-FU in reducing the available repair processes and distribution of the BrUdR in and around the 9L cells (32% of the total subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…5‐FU, a chemotherapeutic agent has been using as a treatment for a variety of tumor types nowadays, both alone and in combination with other drugs. Researchers confirmed that 5‐FU can sensitize the cells to ionizing radiation that is depended directly with the level of halogenated pyrimidine that incorporated into DNA (in vitro and in vivo studies). Although the molecular mechanisms of 5‐FU radiosensitization are not clear it is assumed that 5‐FU sensitizes cells through enhancing the formation of double‐strand break .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5‐FU, a chemotherapeutic agent has been using as a treatment for a variety of tumor types nowadays, both alone and in combination with other drugs. Researchers confirmed that 5‐FU can sensitize the cells to ionizing radiation that is depended directly with the level of halogenated pyrimidine that incorporated into DNA (in vitro and in vivo studies). Although the molecular mechanisms of 5‐FU radiosensitization are not clear it is assumed that 5‐FU sensitizes cells through enhancing the formation of double‐strand break .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, more and more attention of researchers has been attracted to radiosensitizers, which lower the radiation dose‐response threshold for cancer cells without increasing the normal tissue radiosensitivity . To obtain this result the most effective approach is to use halogenated pyrimidines, 5‐fluorouracil (5‐FU) . 5‐FU is commonly used as an anticancer drug for cancer cells, which can be used with X‐ray.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanoparticles exhibit preferential absorption of kilovoltage (or low) energy x-rays due to high photoelectric cross section of the nanoparticle relative to low Z atoms (C, H, N, O etc) in tissues resulting in superior tumor cell treatment and normal tissue sparing (Retif et al 2015, Liu et al 2018. Nanoparticle radiosensitisation of megavoltage x-rays has also been documented (Mcdonald et al 2018) and was attributed to underlying differences in the dose-enhancement on the nanoscale (Mcmahon et al 2011) or due to increasing radiochemical activity in the cellular environment (Guerreiro et al 2019).…”
Section: Introductionmentioning
confidence: 99%